RADIO FREQUENCY IDENTIFICATION AND IMAGE-BASED FACIAL IDENTIFICATION AS AN EMPLOYEE ATTENDANCE SYSTEM - Raden Andy Kurniawan; Zaky, Umar (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2020)
The current development of microcontroller technology can be used to build a presence system for employees. The employee attendance system uses radio frequency identification and facial identification which is designed and built to make it easier to do attendance data recording, so that the data obtained can be precise and accurate. Data collection techniques, namely by interview and observation. The application development process uses the PHP and Python programming languages ​​with Visual Studio Code software applications, Arduino Uno, MySQL software as a database server, and XAMPP as a support. The input used in this system is the employee's personal data and the results of employee face data retrieval which are stored in the .jpg format. The faces taken were taken from 4 people where each face was taken 20 face samples. The results are in the form of web and applications that will provide solutions to existing problems. The conclusion of this application makes it easy to do the recording and attendance, and minimize the fraud committed by employees. Retrieval of face data was taken as much as 20 data with the highest level of accuracy was 87% when the presence test was carried out.